Peranan Daily Work Report dalam Bongkar Muatan Curah Kering pada PT. Wahana Intradermaga Niaga Belawan - Daniel Marthin W Sihombing; Nurmaliana Sari Siregar (Jurnal Manajemen Bisnis Era Digital, 2025)
Belawan Port is a strategic port in North Sumatra with export-import activities reaching 5,000 tons per year, making it an important terminal in supporting international trade and regional economic growth. This research examines the role of daily work reports in dry bulk cargo unloading operations at PT. Wahana Intradermaga Niaga Belawan as a Stevedoring Company (PBM) responsible for ensuring the smooth process of loading and unloading at the port. The research methodology employs library research approach and direct field observation. The dry bulk cargo unloading process involves the inaportnet system and operates for 24 hours with three work shifts. Activities include four main types of operations: stevedoring (transferring cargo from ship to wharf), cargodoring (transfer from wharf to warehouse), delivery (shipment outside the port), and receiving (acceptance from factory to warehouse). The daily report document is a list of all cargo unloading activities during 24 hours at wharf 112. Daily work reports function as structured documentation of daily activities, conveying work progress updates, supporting performance monitoring, and serving as a reference for operational evaluation. The report's usefulness includes strengthening accountability, reducing misunderstandings, early problem detection, consistency in task implementation, and orderly documentation of unloading activities. Operational preparation involves permit processing according to port regulations, equipment preparation such as hopper, conveyor belt, grab, excavator, wheel loader, and sling ropes. Supporting documents include Bill of Lading, Cargo List, Cargo Manifest, and various operational reports. Obstacles faced include the influence of bad weather, human resource constraints related to workforce professionalism, and land transportation barriers. Related institutions include cargo owners, PBM, shipping agents, port authorities, PT. Pelindo Belawan, and EMKL companies that coordinate to ensure smooth dry bulk cargo unloading operations.